STUDI KASUS: FAKTOR PEMICU SERING BUANG AIR KECIL DAN DAMPAKNYA TERHADAP KUALITAS TIDUR IBU HAMIL TRIMESTER III - Kotarumalos, Sitti Sarifah; Hermanses, Sitti Suharni (Jurnal Kebidanan, 2024)
Pregnancy is a time of significant physiological, psychological, and emotional changes in a woman's body. As the fetus develops, the mother's body undergoes changes that affect various bodily functions, one of which is increased urinary frequency. This case study was conducted on 10 third-trimester pregnant women who experienced frequent urination and its impact on their sleep. The study aims to identify triggering factors and assess the impact on sleep quality in third-trimester pregnant women. Sleep disturbances caused by frequent waking to urinate can negatively affect the physical and mental well-being of pregnant women. The study involved several third-trimester pregnant women who reported frequent nighttime urination. The results show that the majority of the participants woke up 2-5 times each night to urinate, leading to fragmented sleep and reduced sleep duration and efficiency. These sleep disturbances are associated with excessive daytime sleepiness, fatigue, and a decline in the quality of life of the pregnant women. Additionally, the findings also indicate that physical factors such as the enlarged uterus pressing on the bladder and hormonal changes play a significant role in increasing urinary frequency. The obstetric care management in this case study recommends interventions such as education on fluid intake regulation, Kegel exercises, and relaxation techniques like yoga to reduce sleep disturbances. It is hoped that this case study can provide insights for healthcare professionals to offer more effective management to improve the sleep quality and overall well-being of pregnant women.